Cryopreservation of zygotic embryos of the Brazilian Green Dwarf coconut - Lédo, Ana da Silva; Jenderek, Maria; Skogerboe, Dianne; Staats, Elise; Machado, Caroline de Araújo; Oliveira, Leila Albuquerque Resende de (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate rewarming procedures and recovery media for Brazilian Green Dwarf coconut (Cocos nucifera) embryos cryopreserved by vitrification. The rewarming procedures evaluated were: T1, water bath at 38±2°C; and T2, unloading solution consisting of Y3 medium + 1.2 mol L-1 sucrose. The recovery media assessed were: M1, Y3 medium + 45 g L-1 sucrose + 1 mg L-1 gibberellic acid + 1 g L-1 activated charcoal + 2.2 g L-1 Gelrite; and M2, Y3 medium + 60 g L-1 sucrose + 2.2 g L-1 Gelrite. Rewarming procedures showed no significant effect, and the M1 media induced 72.5% regeneration.